Impaired Baroreflex Function during Orthostatic Challenge in Patients after Spinal Cord Injury - Ondrusova, Katarina; Svacinova, Jana; Javorka, Michal; Novak, Jan; Novakova, Marie; Novakova, Zuzana (Journal of neurotrauma, 2017)
The level of spinal cord injury (SCI) affects baroreflex regulation of blood pressure. While a parasympathetic cardiac chronotropic effect is preserved, baroreflex response could be impaired by sympathetic dysfunction under the SCI level. This study was aimed to evaluate the baroreflex function in SCI patients by the analysis of causal interaction between systolic blood pressure (SBP) and inter-beat intervals (IBI). Blood pressure was continuously recorded in 13 cervical SCI patients (CSCI), nine thoracic SCI (ThSCI) and 13 able-bodied controls (Con) during two phases: sitting (PS) and orthostatic challenge (PO). Beat-to-beat SBP and IBI sequences were obtained from continuous blood pressure recording. Closed loop of SBP-IBI interaction was mathematically opened by bivariate autoregressive model; causal coherence and baroreflex sensitivity (BRS) were calculated in baroreflex direction. Coherence quantifies causal synchronicity between SBP and IBI. The gain of transfer function from SBP to IBI represents BRS. PS (medians of CSCI/ThSCI/Con) coherence was 0.28/0.33/0.25 (no significant difference) and PS BRS was 6.98/7.54/6.66 (no difference). PO coherence was 0.18/0.58/0.45 (CSCI < ThCSI and Con; p < 0.01) and PO BRS was 2.38/5.87/6.22 (CSCI < ThCSI and Con; p < 0.01). For position change effect, there was no change in CSCI coherence; for ThSCI and Con, PS < PO (p < 0.05). For BRS in the CSCI group, PS < PO (p < 0.01); for ThSCI and Con, there was no change. BRS and coherence correlated negatively with SCI level (p < 0.01). In conclusion, baroreflex dysfunction in SCI patients was detected using causal analysis methods during orthostatic challenge only. Baroreflex dysfunction is probably an important mechanism of the more expressed blood pressure decrease associated with CSCI. The severity of autonomic dysfunction was related to SCI level.
Keywords: dospělí; Baroreflex; Female; Adult; ženské pohlaví; lidé; postura těla; poranění míchy; krevní tlak; Spinal Cord Injuries; spinal cord injury; Male; Posture; orthostasis; baroreflex; baroreflex sensitivity; mužské pohlaví; Blood Pressure; causal analysis; Humans